Public Service Quality: A Study on the Integrated Police Service Center (SPKT) at Polres Metro Jakarta Pusat (SERVQUAL) - Lenina Olin; Oscarius Yudhi Ari Wijaya; Novi Indah Earlyanti; Elvianus Laoli (LP2M IAIN Palopo, 2026)
The quality of public services provided by the Integrated Police Service Center (SPKT) of the Central Jakarta Metro Police can be assessed by examining the gap between public perceptions and expectations of the services delivered. SPKT represents a core functional unit within the police institution and serves as the frontline of police services, playing a crucial role in shaping public perceptions of institutional professionalism and legitimacy. Based on this context, the main issue addressed in this study concerns the extent to which the quality of SPKT services meets the ideal standards expected by the community. The analysis in this study is grounded in two main theoretical frameworks, namely New Public Management and Service Quality Theory, with the SERVQUAL model—comprising five dimensions: tangibles, reliability, responsiveness, assurance, and empathy—used as the analytical approach. This study adopts a quantitative approach, employing a survey method involving 150 respondents. The findings indicate that all SERVQUAL dimensions show a statistically significant relationship between perceptions and expectations (p < 0.05). Although the perception scores fall within a good category (above a score of 4), all dimensions still exhibit negative gaps. The tangibles dimension shows the largest gap, while responsiveness is the closest to meeting public expectations.